Antimicrobial and Antibiofilm Effects of Human Amniotic/Chorionic Membrane Extract on Streptococcus pneumoniae - Yadav, Mukesh K.; Go, Yoon Y.; Kim, Shin Hye; Chae, Sung-Won; Song, Jae-Jun (Frontiers in Microbiology, 2017)
Background: Streptococcus pneumoniae colonize the human nasopharynx in the form of biofilms. The biofilms act as bacterial Background: Streptococcus pneumoniae colonize the human nasopharynx in the form of biofilms. The biofilms act as bacterial reservoirs and planktonic bacteria from these biofilms can migrate to other sterile anatomical sites to cause pneumonia, otitis media (OM), bacteremia and meningitis. Human amniotic membrane contains numerous growth factors and antimicrobial activity; however, these have not been studied in detail. In this study, we prepared amniotic membrane extract and chorionic membrane extract (AME/CME) and evaluated their antibacterial and antibiofilm activities against S. pneumoniae using an in vitro biofilm model and in vivo OM rat model. Materials and Methods: The AME/CME were prepared and protein was quantified using DC™ (detergent compatible) method. The Minimum inhibitory concentrations (MICs) were determined using broth dilution method, and the synergistic effect of AME/CME with Penicillin-streptomycin was detected checkerboard. The in vitro biofilm and in vivo colonization of S. pneumoniae were studied using microtiter plate assay and OM rat model, respectively. The AME/CME-treated biofilms were examined using SEM and confocal microscopy. To examine the constituents of AME/CME, we determined the proteins and peptides of AME/CME using tandem mass tag (TMT)-based quantitative mass spectrometry (MS). Results: AME/CME treatment significantly (p<0.05) inhibited S. pneumoniae growth in planktonic form and in biofilms. Combined application of AME/CME and Penicillin-streptomycin solution had a synergistic effect against S. pneumoniae. Biofilms grown with AME/CME were thin, scattered, and unorganized. AME/CME effectively eradicated pre-established pneumococci biofilms and has a bactericidal effect. AME treatment significantly (p<0.05) reduced bacterial colonization in the rat middle ear. The proteomics analysis revealed that the AME/CME contains hydrolase, ribonuclease, protease, and other antimicrobial proteins and peptides. . Conclusion: AME/CME inhibits S. pneumoniae growth in the planktonic and biofilm states via its antimicrobial proteins and peptides. AME/CME are non-cytotoxic, natural human product; therefore, they may be used alone or with antibiotics to treat S. pneumoniae infections.